Pengaruh Tax Avoidance dan Risiko Pajak Terhadap Biaya Utang pada Perusahaan Manufaktur yang Terdaftar Di Bei Tahun 2016-2020 - Fauziah Zamifa; Nuramalia Hasanah; Hera Khairunnisa (Department of Accounting, Faculty of Economics & Business, 2022)
This study aims to determine the effect of tax avoidance and tax risk on cost of debt. The independent variables in this study are tax avoidance and tax risk. The dependent variable is cost of debt. Data used in this study from financial statement of manufacturing companies listed on Indonesia Stock Exchange during 2016-2020. The amount of sample used 43 firms with purposive sampling during 2016-2020. The analytical method used in this study is multiple linear regression analysis which processed by using SPSS 25 software application. The results of this research find that tax avoidance has no effect on cost of debt. Tax risk has a positive significant on cost of debt.